Examining investor reactions to appointments of Black top management executives and CEOs. (10th June 2021) - Gligor, David M.; Novicevic, Millorad; Feizabadi, Javad; Stapleton, Andrew
Abstract: Research summary: The authors investigated investor reactions to the appointment of Black executives. The results indicate that investors respond: (1) more negatively to the announcement of Black CEO appointments than to White CEO appointments, (2) more negatively to the announcement of the Black top management team (TMT) appointments than to White TMT appointments, (3) more negatively to the announcement of Black CEO appointments than to Black TMT appointments, and (4) more negatively to the announcement of Black CEO appointments who are promoted from outside the firm than to the announcement of Black CEO appointments who are promoted from inside the firm. Moreover, the post‐hoc analysis revealed that investors react more negatively to the TMT appointment of Black executives than to the TMT appointment of Latino or Asian executives. Our results show the negative association between the appointment of Black executives and investors' reactions, and we hope it sparks future research examining causal factors and their potential solutions. Managerial summary: Investors react more negatively to the announcement of Black CEO appointments than to White CEO appointments, and more negatively to the announcement of Black CEO appointments who are promoted from outside the firm than to the announcement of Black CEO appointments who are promoted from inside the firm. Moreover, investors react more negatively to TMT appointments of Black executives than to TMT appointments of White, Latino, or Asian executives.